To avoid or to engage : testing the spiral of silence theory using hypothetical and experimental settings - Cha, Ee Ling (2011)
Using the spiral of silence as a theoretical framework, we conducted a two-part study to examine Singaporeans’ opinion expression in a traditional hypothetical setting (i.e., a survey), and in a real setting (i.e., an experiment). To provide a critical examination of opinion expression, we conceptualized individuals’ willingness to express their minority opinion in two dimensions: The use of avoidance and engagement opinion expression strategies. In Study One, we examined individuals’ willingness to employ opinion engagement strategies using secondary data analysis of a nationally representative computer-assisted telephone interviewing survey, on the issue of reprogenetics. Results indicated that fear of isolation, issue salience, attitude strength, and traditional news attention were significantly associated with respondents’ willingness to use opinion engagement strategies in a hypothetical face-to-face situation. In Study Two, we investigated the relationship between social anonymity, and the use of engagement and avoidance opinion expression strategies, in real computer-mediated communication discussion settings. Three levels of social anonymity were manipulated for the experiment, and undergraduates from Nanyang Technological University participated in an actual online group discussion for 30 minutes on the issue of foreign talent. Avoidance and engagement opinion expression strategies were further broken down into six and five action categories respectively for coding. Content analysis of transcripts indicated that social anonymity and future opinion congruency were significantly associated with opinion expression. Findings suggest that the lack of visual and status cues, rather than perceived anonymity, were more likely to elicit opinion expression. Future research should consider coming to a consensus on the measurement of silence on online platforms.